معايير تقييم الأداء التنموي لصناديق الاستثمار الإسلامية - Osamah Hashem; Azman Mohd Noor (Institute of Islamic Banking and Finance, International, 2024)
International Journal of Al-Turath In Islamic Wealth And Finance Volume 2 No.3 Page (40-95)